This Battlefield Called My Body: Warring over the Muslim Female - Medina, Jameelah (Religions, 2014)
This communication centers on the argument that there is an ideological tug-of-war over the Muslim female body. The author discusses how religious and secular patriarchies, as well as feminism all make claims to the bodies of Muslim women and purport to know what is best for her. With particular focus on the headscarf and using comparisons with how non-Muslim women’s bodies are fought over, the author argues that there is a common thread connecting the warring sides as they each employ patriarchal and imperialist views of the Muslim woman that attempt to consume her agency. As the author examines the personal agency and veiling motives of Muslim woman, she counters the idea of Muslim women as passive recipients of mainstream religious and secular narratives imposed upon them by sharing different ways in which they self-author their own narratives in a post-9/11 USA.